Threatening and nurturing mental health: insights from Danish elite athletes on the dynamic interplay of factors associated with their mental health - Küttel, Andreas; Storm, Louise K.; Stambulova, Natalia; Henriksen, Kristoffer (Frontiers in Sports and Active Living, 2024)
Introduction Numerous factors have been identified that potentially influence athletes' mental health. Given the predominant focus in the literature on athletes' mental health risk factors, our study aimed to explore elite athletes' perceptions of factors associated with their mental health and thriving based on the combination of holistic developmental and ecological approaches. Methods Seven Danish international elite athletes representing diverse sports were interviewed twice. The initial interview delved into their retrospective perspectives on career and mental health development, while the subsequent interview, conducted two months later, centered on recent events. Results Thematic analysis yielded a map outlining four overarching themes. Elite sport was perceived as a (1) relentless performance context marked by rigorous demands, which evoked (2) personal reactions among athletes characterized by heightened expectations, self-blame, and anxiety. In response to these challenging demands, athletes have cultivated (3) coping resources and strategies over the course of their careers, such as self-reflection, emphasis on recovery, planning and prioritization skills, and passion for their sport. Nonetheless, the development of these resources and strategies was a gradual process, often informed by past experiences of mental health difficulties during adolescence. Additionally, they have found support for their mental health within a (4) nurturing environment consisting of supportive coaching, camaraderie among teammates, guidance from experts, and caring relationships. Discussion The findings of this study highlight the complex interplay of factors affecting mental health and emphasize the need for creating supportive environments that help athletes manage the intense demands of elite sport.